The Development of Audio-Visual Media on the Memory Retention of Early Childhood at RA Darussalam - Hasan, Fadilah; Mukhlis, Mukhlis; Harahap, Sartika Dewi (CV. Edutechnium Indonesia, 2025)
This study explores audio-visual media's development process and effectiveness in improving memory retention among early childhood learners. Using a Research and Development (R&D) approach based on the Borg and Gall model (2003), the research followed ten stages, including preliminary studies, planning, product development, implementation, and evaluation. The media developed consisted of educational animated videos presenting letters and numbers through visual elements, audio, and interactive activities tailored to the learning characteristics of young children. The validation results showed a feasibility score of 97.14%, categorized as very high. The trial was conducted at RA Darussalam and involved both teachers and students. Observations and interviews revealed that the children were enthusiastic, focused, and actively engaged in learning. They could answer questions and recall information effectively after using the media. Teachers noted that the press enhanced student participation and engagement in classroom activities. The audio-visual media created an enjoyable learning atmosphere and stimulated children's cognitive and social abilities. It also helped reduce learning fatigue and increased students' interest in the subject. Based on these findings, the media is considered adequate for early childhood education, particularly in strengthening memory retention and understanding of basic concepts.